2016
DOI: 10.7243/2055-2394-3-1
|View full text |Cite
|
Sign up to set email alerts
|

A controversy on HLA-G and B-cell malignancies?

Abstract: In solid tumors HLA-G is a clear immune-escape molecule inhibiting innate and adaptive effectors. This is not systematically demonstrated for B-cell malignancies, leading to a confused overall role for HLA-G in cancer likely due to the fact that malignant B-cells are as much of immune origin as the anti-tumoral effectors themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In contrast, several studies found evidence of a relationship between HLA-G and better prognosis for B cell neoplasms [53][54]. These different observations can be attributed to the capacity of B cells to express ILT2 and therefore inhibit the proliferation of malignant B cells [55]. The fate of HLA-G interaction with its receptor on malignant B cells is determined by the balance between HLA-G-driven inhibition on these cells (as immune effector cells) and the antiproliferative effect on these cells (as target malignant cells) [55].…”
Section: Hla-g As a Target In Cancer Therapymentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, several studies found evidence of a relationship between HLA-G and better prognosis for B cell neoplasms [53][54]. These different observations can be attributed to the capacity of B cells to express ILT2 and therefore inhibit the proliferation of malignant B cells [55]. The fate of HLA-G interaction with its receptor on malignant B cells is determined by the balance between HLA-G-driven inhibition on these cells (as immune effector cells) and the antiproliferative effect on these cells (as target malignant cells) [55].…”
Section: Hla-g As a Target In Cancer Therapymentioning
confidence: 97%
“…These different observations can be attributed to the capacity of B cells to express ILT2 and therefore inhibit the proliferation of malignant B cells [55]. The fate of HLA-G interaction with its receptor on malignant B cells is determined by the balance between HLA-G-driven inhibition on these cells (as immune effector cells) and the antiproliferative effect on these cells (as target malignant cells) [55]. Heterogeneous patterns of HLA-G expression in different tumors may reflect differences in the biology of different types of tumor, genetic diversity among the populations studied to date, and the sensitivity of methods used to detect HLA-G [56].…”
Section: Hla-g As a Target In Cancer Therapymentioning
confidence: 99%